COMMUNICATION SKILLS USED BY BULGARIAN GENERAL PRACTITIONERS DURING THE MEDICAL CONSULTATION - Tsvetelina Valentinova (Peytchinski Publishing, 2023)
Background: The concept of doctor-patient communication develops from the idea that its main function is to gather information to the idea that it is an interpersonal relationship and interaction. Aim:To evaluate and analyze the opinion of general practitioners on the application of basic communication skills in medical practice in the therapeutic process and in the process of health education of the patient. Material/Methods: An empirical sociological representative survey was conducted among 190 randomly selected family physicians from two regions of the country. Results: Half of the GPs try to motivate patients, and significant differences were found regarding their sex, age and work experience (p=0.004). For chronically ill patients, 96% GPs discuss and offer advice related to healthy life style, daily activities (toilet, nutrition, mobility) or social activities. The doctors often give advice on nutrition (77%) and physical activity (71%). The majority of GPs (90%) report that they can motivate their patients to maintain a healthy lifestyle if there is even a small interest to do it. However, general practitioners still make insufficient use of active listening techniques, maintain poor eye contact during the interview, and perform other activities during the patient's hearing. In addition, physicians rarely involved the patientin discussions for therapy anddecision making. Conclusion: Surveyed physicians report to a significant extent that they are committed to the health education of their patients in the form of advice on a healthy life style. They manage to deal with many of the difficult communication situations in general practice.